Adaptive model predictive control for a delivery quadrotor - Chikasha, Piwai Nigel (My University, 2018)
This work explores the application of Adaptive Model Predictive Control (AMPC) to a quadrotor, given some delivery (varying load) task. In simulations, this is investigated as a pick-and-place task for a delivery quadrotor, then in experiment, as a load-drop-off stabilization task. [Abbreviated Abstract. Open document to view full version]
A Dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the degree of Master of Science, November 2018